THE IMPACT OF ARTIFICIAL INTELLIGENCE ON LABORATORY SERVICES IN SAUDI ARMED FORCES HOSPITALS: ALIGNING WITH VISION 2030 DIGITAL TRANSFORMATION GOALS - Waleed Dhawi Fahad Aldhafeery, Khalid Mohamed Tala Alsammeri, Farhan Hamad Alshammari, Ahmad Mohammed Farhan Alshammari, Hamed Muflih Nagmosh Alanazi, Abdullah Homaid Skhi Al Shammari (Chelonian Research Foundation, 2024)
Artificial intelligence (AI) has emerged as a transformative technology with the potential to revolutionize healthcare delivery, including laboratory services. In Saudi Arabia, the Vision 2030 plan emphasizes the importance of digital transformation and the adoption of innovative technologies to improve healthcare efficiency and quality. This systematic review aims to explore the impact of AI on laboratory services in Saudi Armed Forces hospitals and its alignment with Vision 2030 digital transformation goals. A comprehensive search of electronic databases, including PubMed, Scopus, and Web of Science, was conducted to identify relevant studies published between 2010 and 2023. The search strategy employed a combination of keywords related to AI, laboratory services, Saudi Armed Forces hospitals, and Vision 2030. A total of 22 studies met the inclusion criteria and were included in the review. The findings highlight the potential applications of AI in various aspects of laboratory services, such as automated testing, image analysis, quality control, and data management. Key factors influencing the successful implementation of AI in laboratory services include data quality and standardization, infrastructure and interoperability, workforce development, and governance and regulation. The review also identifies challenges and barriers to the adoption of AI in laboratory services, such as limited resources, ethical and legal concerns, and cultural and organizational resistance. The findings of this review have significant implications for healthcare policy, practice, and research in Saudi Arabia, emphasizing the need for strategic initiatives to support the integration of AI in laboratory services and align with Vision 2030 digital transformation goals.